Sesquiterpene lactones as allelochemicals - Macias, Francisco A.; Fernandez, Adriana; Varela, Rosa M.; Molinillo, Jose M. G.; Torres, Ascension; Alves, Pedro L. C. A. (Amer Chemical Soc, 2006)
Six new sesquiterpene lactones, annuolide H ( 3), helivypolides F, H-J ( 4, 11-13), and helieudesmanolide A ( 6), together with known compounds, were isolated from polar bioactive fractions of Helianthus annuus cv. SH-222 and Stella fresh leaf water extracts. Spectroscopic analysis of the new data for 1,2-anhydroniveusin A and 1-methoxy-4,5-dihydroniveusin A corrects some previous assignments. The compounds were tested using the etiolated wheat coleoptile bioassay, and the most active compounds were assayed in standard target species ( STS) ( Lepidium sativum, Allium cepa, Lactuca sativa, Lycopersicon esculentum, and Triticum aestivum) from 5 x 10(-4) to 10(-5) M. The most phytotoxic compounds were helivypolide F and 15-hydroxy-3-dehydrodeoxyfruticin, both of which have a carbonyl group at C-3 conjugated with two double bonds.